{4-Hydroxy-N `-[(2-oxido-1-naphthyl-kappa O)methylidene]benzohydrazidato-kappa(2) N `,O}dimethyltin(IV) - Abu Affan, M.; Sam, N.B.; Ahmad, F.B.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent but very similar molecules comprise the asymmetric unit of the title compound, [Sn(CH3)(2)(C18H12N2O3)]. Each Sn atom is coordinated by two methyl groups and two O atoms and an N atom from the dinegative tridentate ligand. The resultant C2NO2 donor set defines a coordination geometry intermediate between square-pyramidal and trigonal-pyramidal, with a small tendency towards the former. Zigzag chains running along the a axis mediated by O-H center dot center dot center dot N hydrogen bonding characterize the crystal packing. These are connected into layers in the ab plane by a combination of C-H center dot center dot center dot N and pi-pi [centroid-centroid distances = 3.658 (2) and 3.6740 (18) angstrom] interactions. The layers are connected along the c axis via C-H center dot center dot center dot O interactions.